2011
DOI: 10.1007/s10530-011-0097-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of ant-seed dispersal mutualisms by the invasive Asian needle ant (Pachycondyla chinensis)

Abstract: By disrupting the structure of native ant assemblages, invasive ants can have effects across trophic levels. Most studies to date, however, have focused on the impacts just two species (Linepithema humile and Solenopsis invicta). The impacts of many other invasive ant species on ecological processes in their introduced range are unknown. In this study we tested the hypothesis that the invasive ant Pachycondyla chinensis disrupts ant-seed dispersal mutualisms by displacing native ant species, especially the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 53 publications
2
59
0
1
Order By: Relevance
“…Disruptions of mutualistic systems (pollination and seed dispersal) have often been documented, but their ecological implications have remained less extensively studied (Traveset and Richardson 2006;Rodríguez-Cabal et al 2011;Markl et al 2012;Traveset et al 2012). For example, mutualistic disruptions can induce cascading effects on biodiversity, but they remain quite unknown in an ecological context (Aslan et al 2013), especially on islands.…”
mentioning
confidence: 99%
“…Disruptions of mutualistic systems (pollination and seed dispersal) have often been documented, but their ecological implications have remained less extensively studied (Traveset and Richardson 2006;Rodríguez-Cabal et al 2011;Markl et al 2012;Traveset et al 2012). For example, mutualistic disruptions can induce cascading effects on biodiversity, but they remain quite unknown in an ecological context (Aslan et al 2013), especially on islands.…”
mentioning
confidence: 99%
“…Warren and Chick (2013) showed how changing climates influenced the distribution of native ant species along an elevation gradient in southern United States, with consequences for seed dispersal mutualisms. In addition, several studies in low elevation forest sites have demonstrated how the Asian needle ant (Brachyponera chinensis) alters native ant communities and seed-dispersal mutualisms (e.g., Rodriguez-Cabal et al 2012) and models suggest that this invasive ant is likely to move upward in both latitude and elevation (Bertelsmeier et al 2013). …”
Section: New Multi-species and Multi-trophic Interactionsmentioning
confidence: 99%
“…In this context, our mesocosm approach is unique; most previous research has compared seed removal between invaded and uninvaded sites (e.g. [6,43]). Results in these previous studies may be confounded by pre-existing differences between invaded and uninvaded sites or a higher overall density of ants in invaded sites [34,36].…”
Section: Introductionmentioning
confidence: 99%